2013
DOI: 10.4172/2165-7866.1000121
|View full text |Cite
|
Sign up to set email alerts
|

Extending UML for Modeling Data Mining Projects (DM-UML)

Abstract: Existing Data Mining process models propose one way or another of developing projects in a structured manner, trying to reduce their complexity through effective project management. It is well-known in any engineering environment that one of the management tasks that helps to reduce project problems is systematic project documentation, but few of the existing Data Mining processes propose their documentation. Furthermore, these few remark the need of producing documentation at each phase as an input for the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Consequently, the findings of the study comprehended that the productivity growth of the Egyptian banks was declined over the whole study period at the rate of 2.55%. Baten et al (2015) analyzed the efficiency and total factor productivity changes of the banking sector in Bangladesh based on secondary data using the Malmquist based data envelopment analysis method. The findings revealed that state-owned banks registered the highest cost inefficiency and profit efficiency in comparison to the private banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, the findings of the study comprehended that the productivity growth of the Egyptian banks was declined over the whole study period at the rate of 2.55%. Baten et al (2015) analyzed the efficiency and total factor productivity changes of the banking sector in Bangladesh based on secondary data using the Malmquist based data envelopment analysis method. The findings revealed that state-owned banks registered the highest cost inefficiency and profit efficiency in comparison to the private banks.…”
Section: Literature Reviewmentioning
confidence: 99%